Interventions to improve adherence to reporting guidelines in health research: a scoping review protocol - Blanco, D; Kirkham, J; Altman, D; Moher, D; Boutron, I; Cobo, E (BMJ Publishing Group, 2017)
Introduction There is evidence that the use of some reporting guidelines, such as the Consolidated Standards for Reporting Trials, is associated with improved completeness of reporting in health research. However, the current levels of adherence to reporting guidelines are suboptimal. Over the last few years, several actions aiming to improve compliance with reporting guidelines have been taken and proposed. We will conduct a scoping review of interventions to improve adherence to reporting guidelines in health research that have been evaluated or suggested, in order to inform future interventions. Methods and analysis Our review will follow the Joanna Briggs Institute scoping review methods manual. We will search for relevant studies in MEDLINE, EMBASE and Cochrane Library databases. Moreover, we will carry out lateral searches from the reference lists of the included studies, as well as from the lists of articles citing the included ones. One reviewer will screen the full list, which will be randomly split into two halves and independently screened by the other two reviewers. Two reviewers will perform data extraction independently. Discrepancies will be solved through discussion. In addition, this search strategy will be supplemented by a grey literature search. The interventions found will be classified as assessed or suggested, as well as according to different criteria, in relation to their target (journal policies, journal editors, authors, reviewers, funders, ethical boards or others) or the research stage at which they are performed (design, conducting, reporting or peer review). Descriptive statistical analysis will be performed. Ethics and dissemination A paper summarising the findings from this review will be published in a peer-reviewed journal. This scoping review will contribute to a better understanding and a broader perspective on how the problem of adhering better to reporting guidelines has been tackled so far. This could be a major first step towards developing future strategies to improve compliance with reporting guidelines in health research.